Ovarian cancer-derived exosomes promote tumour metastasis in vivo: an effect modulated by the invasiveness capacity of their originating cells. (5th July 2019) - Alharbi, Mona; Lai, Andrew; Guanzon, Dominic; Palma, Carlos; Zuñiga, Felipe; Perrin, Lewis; He, Yaowu; Hooper, John D.; Salomon, Carlos
Abstract : Exosomes are small nanovesicles that carry bioactive molecules which can be delivered to neighbouring cells to modify their biological functions. Studies have showed that exosomes from ovarian cancer (OVCA) cells can alter the cell migration and proliferation of cells within the tumour microenvironment, an effect modulated by the invasiveness capacity of their originating cells. Using an OVCA cell line xenograph mouse model, we showed that exosomes derived from a high invasiveness capacity cell line (exo-SKOV-3) promoted metastasis in vivo compared with exosomes from a low invasiveness capacity cell line (exo-OVCAR-3). Analysis from an in vivo imaging system (IVIS) revealed that exo-SKOV-3 formed metastatic niches, whereas exo-OVCAR-3 formed colonies of clustered cells close to the site of injection. Interestingly, kinetic parameters showed that the half-maximal stimulatory time (ST50 ) of tumour growth with exo-OVCAR-3 (4.0 ± 0.31 weeks) was significantly lower compared with the ST50 in mice injected with exo-SKOV-3 (4.5 ± 0.32 weeks). However, the number of metastic nodes in mice injected with exo-SKOV-3 was higher compared with exo-OVCAR-3. Using a quantitative mass spectrometry approach (SWATH MS/MS) followed by bioinformatics analysis using the Ingenuity Pathway Analysis (IPA), we identified a total of 771 proteins. Furthermore, 40 of these proteins were differentially expressed in tumour tissues from mice injected with exo-SKOV-3 compared with exo-OVCAR-3, and associated with Wnt canonical pathway (β-catenin). Finally, we identified a set of proteins which had elevated expression in the circulating exosomes in association with tumour metastasis. These observations suggest that exosomal signalling plays an important role in OVCA metastasis.